Determining the Timing of Investment in Mutual Fund Products using the Double Exponential Smoothing Model - Achmad Muchayan; I Putu Artaya; Made Kamisutara (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: As we know, COVID-19 affects the economy of most of the world, one of the investment media that continues to grow is mutual fund investment. This study aims to find the right time to invest by studying data in the previous period. Design/methodology/approach: In this study, we collect daily data on Net Asset Value (NAV) prices from January to September 2021, by analyzing calculations using the double exponential smoothing method to predict the time with the lowest price for investing. Findings: The results showed that this study was able to predict the right time to invest in mutual funds using the Holt Double Exponential Smoothing method using the actual smoothing data parameter of 0.9 (alpha) and the trend data smoothing parameter of 0.1 (beta) with produces a Mean Absolute Percentage Error (MAPE) value of 0.85343. The right time to invest in this research is determined on November 2, 2021 with an estimated net asset value (NAV) of 2348.644032. Paper type: Research paper Keywords: Mutual Fund, Investment Time, Investment Tool, Double Exponential Smoothing.